2011
DOI: 10.1103/physrevb.84.054452
|View full text |Cite
|
Sign up to set email alerts
|

120helical magnetic order in the distorted triangular antiferromagnetα-CaCr2O

Abstract: α-CaCr2O4 is a distorted triangular antiferromagnet. The magnetic Cr 3+ ions which have spin-3/2 and interact with their nearest neighbors via Heisenberg direct exchange interactions, develop long-range magnetic order below TN = 42.6 K. Powder and single-crystal neutron diffraction reveal a helical magnetic structure with ordering wavevector k = (0, ∼ 1/3, 0) and angles close to 120• between neighboring spins. Spherical neutron polarimetry unambiguously proves that the spins lie in the ac plane perpendicular t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 26 publications
5
51
0
Order By: Relevance
“…In low temperature, the corresponding magnetic susceptibilities in H⊥a and H a have been measured (not shown). And both behave very similar as the bulk sample, which is consistent with the published data on the isostructural crystals of α-CaCr 2 O 4 by Toth et al [23] As shown in Fig. 6, in zero field, ǫ a (T) decreases gradually on cooling.…”
Section: Magnetoelelctric Coupling In Bulk α-Srcr2o4supporting
confidence: 90%
See 2 more Smart Citations
“…In low temperature, the corresponding magnetic susceptibilities in H⊥a and H a have been measured (not shown). And both behave very similar as the bulk sample, which is consistent with the published data on the isostructural crystals of α-CaCr 2 O 4 by Toth et al [23] As shown in Fig. 6, in zero field, ǫ a (T) decreases gradually on cooling.…”
Section: Magnetoelelctric Coupling In Bulk α-Srcr2o4supporting
confidence: 90%
“…The antiferromagnetic humps in χ(T ) are clearly observed on both compounds, very similar to that of α-SrCr 2 O 4 . The neutron diffraction measurements on the powder and single crystal samples of α-CaCr 2 O 4 [22,23] have revealed a long-range incommensurate proper-screw-type helimagnetic ground state, which is almost identical to that observed in α-SrCr 2 O 4 . [24] An analogous helical spin picture in α-BaCr 2 O 4 was just proposed based on the recent neutron powder diffraction by Hardy et al [25] The high similarity of magnetic structures in the α-MCr 2 O 4 family accounts for their analogous magnetic properties, which comes from the basal structure of the quasi-2D triangular CrO 2 layers.…”
Section: B α-Phase Cacr2o4 and Bacr2o4mentioning
confidence: 70%
See 1 more Smart Citation
“…It possesses an orthorhombic crystal structure described by the space group P mmn (D 13 2h ), in which chromium ions form a distorted triangular lattice [62]. Below T N an incommensurate magnetic order appears with the wave vector k = (0, 0.3317, 0) and magnetic moments rotating in the ac plane [60,62].…”
Section: α-Cacr 2 Omentioning
confidence: 99%
“…Thus, two different IR's ∆ 1 and ∆ 2 condense at T N as a result of a weakly first order phase transition [60,61]. However, such transition is only possible if the coefficients at a ) and (0.4932, 1 4 , 0.0046) [62]. The permutational representation for both of them in the (0, 1 3 , 0) point of the Brillouin zone is given by ∆ 1 ⊕∆ 2 ⊕∆ 3 ⊕∆ 4 .…”
Section: α-Cacr 2 Omentioning
confidence: 99%